Comparison between Conventional Method and Cradle-to-Cradle Method of Waste Management Method - Noor Yasmin Zainun; Iffah Hafizah Yusri (Journal of Structural Monitoring and Built Environment, 2024)
Concrete is a widely used material in the construction industry. Rice husk ash and coal bottom ash are by-product materials chosen to alternate the use of cement and sand in concrete production. Concerns about the long-term performance of seawater concrete structures incorporated with RHA-CBA have been obstacles to the developing uses of sustainable concrete due to the scarcity of knowledge and test data. Thus, the long-term performance of seawater concrete consisting of RHA as cement replacement and CBA as sand replacement on compressive strength and carbonation was evaluated in this study. To accomplish the study’s goal, existing specimens aged 1 year and 4 months, and 2 years with different mixture series were used. In the mixture, seawater was utilized to fully replace freshwater, along with 10% RHA used to replace cement. Additionally, 10% to 100% CBA replaced the sand with a 10% increment. The specimens consisted of 68 cylindrical concretes in 100 ? 100 mm and 100 ? 200 mm exposed to indoor environmental conditions. Compressive strength and carbonation tests were performed to assess the strength and durability of the concrete. The results indicate that the concretes’ strength grows insignificantly in the atmospheric environment within exposure age. After a prolonged period, the specimen’s strength development reduces as the amount of CBA in the concrete mixture increases. Meanwhile, test results revealed that RHA-seawater concrete containing CBA exhibited minimal carbonation after 2 years of aging. Higher incorporation of CBA in the concrete mixture leads to a greater carbonation rate, reducing the concrete’s alkalinity. The findings of this study contribute to the understanding and advancement of long-term performances of sustainable concrete materials for construction practices.